2010
DOI: 10.1177/1545968310390520
|View full text |Cite
|
Sign up to set email alerts
|

Abbreviated Environmental Enrichment Enhances Neurobehavioral Recovery Comparably to Continuous Exposure After Traumatic Brain Injury

Abstract: Background Environmental enrichment (EE) is a complex living milieu that has been shown to enhance functional recovery vs. standard (STD) housing after experimental traumatic brain injury (TBI) and therefore may be considered a rodent correlate of rehabilitation. However, the typical EE paradigm consists of continuous exposure to enrichment after TBI, which is inconsistent with the limited time frame in clinical rehabilitation. Objective To determine whether abbreviated EE (i.e., rehabilitation-relevant dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
77
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(92 citation statements)
references
References 49 publications
(114 reference statements)
14
77
1
Order By: Relevance
“…The data revealed that the TBI group receiving EE plus vehicle (i.e., EE alone group) performed significantly better in the acquisition task in the MWM than the vehicle-treated STD housed group, which replicates numerous studies in adult models of TBI. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]36 EE alone, however, did not lead to an increase in memory retention, which is in contrast to that seen in adult models. 23,26,29,33 As reported for Experiment 1, the buspirone (0.1 mg/kg) STD-housed group was also significantly better than the STD vehicle group in the MWM.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…The data revealed that the TBI group receiving EE plus vehicle (i.e., EE alone group) performed significantly better in the acquisition task in the MWM than the vehicle-treated STD housed group, which replicates numerous studies in adult models of TBI. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]36 EE alone, however, did not lead to an increase in memory retention, which is in contrast to that seen in adult models. 23,26,29,33 As reported for Experiment 1, the buspirone (0.1 mg/kg) STD-housed group was also significantly better than the STD vehicle group in the MWM.…”
Section: Discussioncontrasting
confidence: 64%
“…[18][19][20][21][22][23][24][25][26] Likewise, EE has also been shown to confer neurobehavioral and histological benefits in adult male rats after CCI 20,23,[26][27][28][29][30][31][32][33][34] and fluid percussion brain injury. [35][36][37][38][39][40] Recently, the benefits of EE have also been extended to female rats after CCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The workshop leaders focused exclusively on the potential for combinatorial pharmacological agents to promote recovery. While this is a commendable start, there is certainly real potential and value in including non-invasive therapies, such as environmental enrichment (EE) or exercise (Gomez-Pinilla et al, 2011;Griesbach et al, 2009;Hamm et al, 1996;Hicks et al, 2002;Hoffman et al, 2008;Kline et al, 2007Kline et al, ,2010Matter et al, 2011;Passineau et al, 2001;de Witt et al, 2011), in combinational therapy paradigms for promoting recovery and perhaps augmenting the pharmacological effects, particularly in rehabilitation settings.…”
Section: Introductionmentioning
confidence: 99%
“…This paradigm has consistently shown improvements in behavioral and histological outcome after brain trauma and can therefore be considered a reasonable approach to preclinical rehabilitation. Importantly, the benefits conferred by EE span clinically-relevant models of experimental TBI, such as controlled cortical impact (CCI; Chen et al, 2005;de Witt et al, 2011;Hoffman et al, 2008;Kline et al, 2007Kline et al, ,2010Matter et al, 2011;Sozda et al, 2010) and fluid percussion (Hamm et al, 1996;Hicks et al, 2002;Gaulke et al, 2005;Giza et al, 2005;Maegele et al, 2005;Passineau et al, 2001). The second therapy in this combined treatment approach is the systemic administration of the serotonin 1A (5-HT 1A )-receptor agonist buspirone.…”
Section: Introductionmentioning
confidence: 99%